Aplikasi Metode Geolistrik Resistivitas untuk Menentukan Zona Lemah (Studi Kasus: Wilayah Episenter Gempabumi di Kecamatan Lalolae, Kabupaten Kolaka Timur) - T. Triani; Sudarwin Kamur; Erfina Erfina (Universitas Andalas, 2026)
Research was conducted on the weak zones at the epicenter of the earthquake in Lalolae District, East Kolaka Regency, utilizing the Wenner 2D resistivity geophysical method. This study involved five measurement lines, each 150 meters in length, with a spacing of 10 meters between electrodes. The data analysis revealed that resistivity values across each line were heterogeneous, ranging from low to high resistivity at varying depths. Low resistivity (<100 Ωm), indicated in blue, corresponds to sandy alluvium resulting from the weathering of schistose rocks, which are classified as weak zones. Medium resistivity (>100 Ωm) is situated above the low resistivity layer and transitions into the high resistivity layer across each measurement traverse, identified as gneiss rock. High resistivity (>200 Ωm) extends along the measurement path at varying depths and is classified as quartzite rock.